Characteristics associated with physical activity capacity and performance in children and adolescents with an acquired brain injury. (16th April 2017) - Baque, Emmah; Barber, Lee; Sakzewski, Leanne; Ware, Robert; Boyd, Roslyn N.
ABSTRACT: Aim : To examine characteristics associated with physical activity capacity and performance in children with acquired brain injury (ABI). Methods : 58 children (32 men; age 11 years 11 months ± 2 years 6 months; Gross motor function classification system [GMFCS] equivalent I = 29, II = 29) >12 months post ABI were recruited. Physical activity capacity measures included: (i) combined score of three 30-second repetition maximum functional strength exercises; (ii) timed up and go; (iii) 6-minute walk test and (iv) high-level mobility assessment tool (HiMAT). Physical activity performance determined time spent in sedentary, light and moderate to vigorous physical activity (MVPA). Full scale intelligence quotient (FSIQ) was assessed using the Wechsler intelligence scale for Children-IV. Regression models were constructed with functional strength score ( n = 56), activity counts/minutes and time spent in MVPA and sedentary ( n = 37). Results : The HiMAT and FSIQ explained 69% of the variance in functional strength. Age explained 12% of the variance in counts/min and 14% of the variance in time spent sedentary. GMFCS explained 10% of the variance in time spent in MVPA. Conclusions : The ability to perform functional strength exercises is associated with mobility beyond independence and adequate intellectual ability for children with ABI. Age was the most significant factor associated with physical activity performance, and interventions should target adolescents with ABI.